2022
DOI: 10.1021/acs.jpcc.2c05210
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Sensing Mechanism of ZnO Nanoparticles through Identifying Intrinsic Defects

Abstract: Progress in crystal growth made ZnO applicable as the next generation of inorganic lightemitting diodes and lasers, which has attracted much attention. Our previous work is a proof that Zn vacancies are occupied by three protons to form V Zn H 3 complexes in high-quality ZnO single crystals. In this work, electron paramagnetic resonance (EPR) and nuclear magnetic resonance (NMR) studies on high-quality ZnO single crystals further confirm that three proton clusters or cations with three positive charges are the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…27 The study of H defects in ZnO single crystals has shown this enormous isotope effect. 28 Protons in −O(H 2 ) groups are accountable for the generation of the W 5+ signal; hence, the H/D exchanging experiments were carried out by soaking the WO 3 samples in D 2 O at 60 °C for 24 h. The EPR spectra in Figure 12 clearly demonstrate that the signal at g = 1.34 is disappeared. This finding is also compatible with the rationale for producing the W 5+ signal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The study of H defects in ZnO single crystals has shown this enormous isotope effect. 28 Protons in −O(H 2 ) groups are accountable for the generation of the W 5+ signal; hence, the H/D exchanging experiments were carried out by soaking the WO 3 samples in D 2 O at 60 °C for 24 h. The EPR spectra in Figure 12 clearly demonstrate that the signal at g = 1.34 is disappeared. This finding is also compatible with the rationale for producing the W 5+ signal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The lifetime of a metal oxide semiconductor can be greatly increased by using deuterium instead of hydrogen . The study of H defects in ZnO single crystals has shown this enormous isotope effect . Protons in −O­(H 2 ) groups are accountable for the generation of the W 5+ signal; hence, the H/D exchanging experiments were carried out by soaking the WO 3 samples in D 2 O at 60 °C for 24 h. The EPR spectra in Figure clearly demonstrate that the signal at g = 1.34 is disappeared.…”
Section: Resultsmentioning
confidence: 99%
“…Isotype heterojunctions have similar majority carriers which contribute to the currents. , As the mobility of holes is much less, a p-p isotype heterojunction is not preferable for high-speed photodetector, whereas a n-n heterojunction would be fruitful. Zinc oxide (ZnO) is one of the most important wide band gap semiconductors for UV photodetector due to its direct band gap, high electron mobility, large exciton binding energy, easy fabrication process, etc. Due to intrinsic point defects and/or hydrogen impurity, undoped ZnO exhibits n-type conductivity. ,, Fabricating a heterojunction of ZnO with Si would offer a scope to detect light in a broad range from UV to NIR with high efficiency without further doping. The optoelectronic properties of ZnO/Si based p-n heterojunctions have been studied widely but only a few reports are available on isotype heterojunction photodetector based on ZnO/Si.…”
Section: Introductionmentioning
confidence: 99%
“…22−25 Due to intrinsic point defects and/or hydrogen impurity, undoped ZnO exhibits n-type conductivity. 24,26,27 Fabricating a heterojunction of ZnO with Si would offer a scope to detect light in a broad range from UV to NIR with high efficiency without further doping. The optoelectronic properties of ZnO/Si based p-n heterojunctions have been studied widely but only a few reports are available on isotype heterojunction photodetector based on ZnO/Si.…”
Section: ■ Introductionmentioning
confidence: 99%